1997
DOI: 10.1021/ef970031o
|View full text |Cite
|
Sign up to set email alerts
|

Release of Chlorine from Biomass at Pyrolysis and Gasification Conditions1

Abstract: The working hypothesis for the study was that the main part of the chlorine in biomass is in an inorganic form and therefore should not vaporize appreciably below the melting point of the corresponding salt (around 700 °C) because the vapor pressure over solid salt is negligible. In the study, biomass fuels (sugarcane trash, switch grass, lucerne, straw rape) were subjected to pyrolysis in a flow of nitrogen, and the weight of the residue and its chlorine content were measured and compared to the original fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(160 citation statements)
references
References 14 publications
13
146
1
Order By: Relevance
“…This is in part corroborated by experimental results from the gasification of other types of waste. 32 That being the case, the fate of the HCl would be in the water of the scrubber, as was the case. Analysis of particulate matter and heavy metals in the clean syngas also indicated low concentrations for these species.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in part corroborated by experimental results from the gasification of other types of waste. 32 That being the case, the fate of the HCl would be in the water of the scrubber, as was the case. Analysis of particulate matter and heavy metals in the clean syngas also indicated low concentrations for these species.…”
Section: Resultsmentioning
confidence: 95%
“…6,32 At the end of the process, gas-phase HCl present in the syngas can easily be absorbed in water to generate an aqueous solution of hydrochloric acid. In fact, the fate is the same for other organic compounds.…”
Section: Gasification Processesmentioning
confidence: 99%
“…Biomass from marine algae is likely to have a high salt content, contributing to corrosion and ash deposition, unless energy-demanding washing processes are carried out (Miles et al 1996;Björkman and Strömberg 1997) The fine particulate nature of dry microalgae may be advantageous in cocombustion with pulverised coal as no additional particle size reduction is required. Non-microalgal biomass particles are normally much bigger than pulverised coal and the amount of energy required for grinding of the biomass to a diameter of less than 1 mm (2-3 % of the heating value) is almost double that required for coal pulverisation (0.9-1.2 % of the heating value).…”
Section: Direct Combustionmentioning
confidence: 99%
“…It has been found that in gasification of biomass HCl and KCl are the dominating chlorine-containing species released in the gas and are formed during the pyrolysis and char oxidation phases. Chlorine exists in several forms in biomass but it is believed that a significant portion is present as the salt KCl which is assumed to begin volatilization above its melting point of approximately 750 ˚C (Bjorkman et al 1997). It was found in experiments performed by Bjorkman, et al that under pyrolysis conditions using N₂, switchgrass retained its chlorine at all temperatures above 400˚C far better than the two types of coal tested (Figure 8-1 (Bjorkman, et al 1997) It was also found that using CO₂ in place of N₂, the same experiments yielded higher chlorine release at temperatures above 800˚C (Bjorkman et al 1997).…”
Section: Conditionsmentioning
confidence: 99%
“…The clinkering problems encountered when gasifying poultry litter are attributed the interaction between the alkali metals, chlorine, and silica present in the fuel (Bjorkman et al 1997;Jenkins et al 1998). The root of the problem is thought to be caused by either one or both of two reactions.…”
Section: Reasons For Clinker Formation and Possible Solutionsmentioning
confidence: 99%